Validation of a Methodology for the Quantification of DON in Feces and Feedstuffs by UPLC as Possible Strategy to Evaluate the Detoxifying Efficacy of a Mycotoxin Adsorbent In Vivo - Bo Yang; Hui Deng; Yiwei Jia; Dong Li; Rudeng Chen; Ruiqing Chen; Jing Zhang; Yan Zhong; Lingxian Yi; Fuhao Wang; Hongjie Cui; Daojin Yu (Toxins)
The study aimed to provide a possible strategy to evaluate the detoxifying efficacy of mycotoxin adsorbents in vivo by analyzing deoxynivalenol (DON) concentration in feces. Fifteen pigs were randomly assigned to five groups (groups A–E, 3 replicates/group). The pigs in each group were fed twice a day for 10 d with 500 g of designed diets (group A, commercial feedstuffs; group B, DON-contaminated (mildewed) feedstuffs; groups C, D, E, mildewed feedstuffs containing 0.2% adsorbent 1, 2, and 3, respectively). For each pig, 2-g fecal samples were collected pre-feeding and analyzed by ultra-performance liquid chromatography. Nondetectable or low concentrations of DON (<1.38 μg/g) were found in fecal samples from groups A and B. High concentrations of DON (>20 μg/g) were detected in six out of twenty fecal batches from pigs in group C. Moderate concentrations of DON (5.54–6.50 μg/g) were detected in one out of twenty fecal batches from pigs in group D and two out of twenty in group E. Based on the predefined evaluation criteria, higher DON concentration and frequency in feces indicate better adsorbent efficacy. Notably, Absorbent 1 demonstrated a more pronounced detoxification efficacy in vivo compared to the other two absorbents.